The competency levels of school principals in implementing knowledge management strategies The views of principals and teachers according to gender variable - Ozmen, Fatma; Muratoglu, Vecihe (Elsevier Science Bv, 2010)
The technological developments and changes which have been experienced in the last decades, have affected significantly the management of organizations. Especially the issue of knowledge management has begun to play a crucial role in ensuring the competitive advantages of the organizations. Therefore, schools, which are already knowledge based organizations, have to develop their knowledge management strategies in order to achieve effective education that meet the requirements of the age. In that context school principalship has received the utmost importance since it is seen as leading authority for accomplishing the educational aims. The main goal of this research is, based on the views of teachers and principals, to determine the competency level of the school principals in implementing some predetermined knowledge management strategies at schools with regard to gender variable. In this study, the views of the subjects have been gathered by a Likert type questionnaire developed by the researchers themselves. The questionnaire consisted of eight dimensions such as Active Knowledge Management, Formation of a Knowledge Team, Formation of a Knowledge Database, Knowledge Mapping, Benchmarking, Formation of a Knowledge Network, Formation of a Knowledge Centre, and Designation of an Executive Responsible for Implementations. The obtained results have revealed that schools generally have some insufficiencies in implementing knowledge management strategies. (c) 2010 Elsevier Ltd. All rights reserved.
2nd World Conference on Educational Sciences (WCES-2010) -- FEB 04-08, 2010 -- Bahceschir Univ, Istanbul, TURKEY
Keywords: Knowledge management; principals; strategies; schools